Individualised left anterior oblique projection for lead implantation into interventricular septum. Issue 2 (12th August 2022) - Narumi, Taro; Naruse, Yoshihisa; Kaneko, Yutaro; Sakakibara, Tomoaki; Sano, Makoto; Mogi, Satoshi; Suwa, Kenichiro; Ohtani, Hayato; Urushida, Tsuyoshi; Saotome, Masao; Maekawa, Yuichiro
Abstract : Objective: We sought to investigate whether it is possible to obtain individualised left anterior oblique (LAO) by preprocedural electrocardiographic parameters and, if so, whether these parameters can help to improve the success rate of right ventricular (RV) lead implantation into the interventricular septum. Methods: In this observational study, we assessed the relationship between preoperative electrocardiographic parameters and the angle of the interventricular septum obtained using thoracic CT. The participants were divided into two groups: a retrospective derivation cohort to derive the optimal formula for the individual septum axis, and a prospective internal validation cohort to which we applied the optimal formula and implanted using the new method. Results: In the retrospective derivation cohort (n=39), the mean angle of individualised LAO assessed by thoracic CT was 53.1°±8.9°, and the preoperative ECG QRS axis was strongly correlated with the interventricular septum axis (R 2 =0.490). LAO projection derived from the preoperative ECG QRS axis confirmed that the RV lead was placed in the interventricular septum during the pacemaker procedure in the prospective internal validation group (n=30). The success rate for placing the RV lead into the interventricular septum was significantly improved in the internal validation cohort (93% vs 64%, p<0.05). In addition, the N-terminal pro-brain natriuretic peptide level decreased significantly after surgery in the interventricular septal indwelling group. Conclusions: Individualised LAO angle derived from the preoperative ECG QRS axis is a new useful and simple method for RV lead implantation into the interventricular septum. Trial registration number: UMIN000045741.